The Correlation Between The Hmar ( Handicapping Malocclusion Assessment Record) Index-Based Malocclusion Severity And The Quality Of Life - Br. Tarigan1, Emdaria Caesa; Sulistyani, Herastuti; Widayati, Aryani; A’yun, Quroti (Jurusan Kesehatan Gigi, Poltekkes Kemenkes Semarang, 2024)
The prevalence of malocclusion in Indonesia is still very high 80%. Malocclusion significantly impacts individuals and society regarding quality of life, anxiety, functional limitations, and emotional conditions. A person with malocclusion may feel isolated in social settings, embarrassed about the appearance of their teeth, or even miss out on employment opportunities. Objective: To investigate the correlation between the HMAR (The Handicapping Malocclusion Assessment Record) index-based malocclusion and the quality of life. Method: This study used the analytical survey method with the cross-sectional design approach. This study was conducted at Dentes of Wirobrajan in Yogyakarta. The sampling was purposive sampling and obtained 34 respondents. The data for malocclusion severity were collected using the Handicapping Malocclusion Assessment Record (HMAR) index and the questionnaire on the quality of life of Oral Health Impact Profile (OHIP-14), and then they were analyzed using the Gamma test. Results: Most respondents had heavy malocclusion and needed treatment were 47.1%. Respondents with a quality of life with poor criteria were 52.9%. Respondents with heavy malocclusion and poor quality of life were 50.0%. The malocclusion severity level with the quality of life and significant value (p = 0.000) and coefficient of correlation at 1.000 had a strong correlation. Conclusion: The malocclusion severity level significantly correlates with the quality of life. The heavier the malocclusion, the poorer the quality of life.